Inflation Thresholds-Financial Development Nexus in South-Eastern Asian Emerging Markets - Tsaurai, Kunofiwa (Journal of Economics and Behavioral Studies, 2017)
This paper investigated the maximum inflation threshold levels beyond which financial development declines in the South-Eastern Asian emerging markets using static panel threshold regression framework proposed by Bick (2010) with data ranging from 1994 to 2014. The negative impact of inflation on financial development is a settled matter in both theoretical and empirical literature. However, this study was prompted by recent literature (Boyd et al., 2001; Abbey, 2012; Kim and Lin, 2010) which argued that the relationship between inflation and financial development is not linear and is characterised by inflation thresholds. Moreover, no previous study that the author is aware of used the approach suggested by Bick (2010) to determine inflation threshold levels and financial development. Among previous inflation-finance studies, the current study is the first one according to the author’s best knowledge to use banking sector, stock market and bond sector development variables as previous studies were narrow focused in their definition of financial development. The study observed that lower levels of inflation is good for financial development whilst higher levels of inflation slows down the rate at which banking sector, stock and bond markets develop. These results agree with the theory underpinning inflation-financial development nexus. South-Eastern Asian emerging economies are therefore urged to implement macroeconomic policies that ensure inflation rates are kept at lower levels that do not stifle financial development.